(untitled) (CIPEEX, 2025)
This research aims to demonstrate how law significantly influences the structuring and functioning of modern societies, considering law a social phenomenon, it is a link between law and society, which ends up being influenced by the elements that surround it. It aims to highlight law as a social fact, and how these principles influence social relations, guaranteeing order, justice, stability, limits and guidelines for each individual’s behavior, and the State within society. Based on the bibliographical review, research was carried out, one of the authors being David Émile Durkheim, sociologist, who reports on how individuals can only act according to the context in which they live, he also talks about when customs are insufficient, it is impossible to do respect the laws. Another author who reports on law and society, Weber sought in his studies to understand society in its historical, cultural and social conditions. As a result, it was possible to recognize the importance of the principles of law as a social fact, we can better understand how law shapes and is shaped by social dynamics, contributing to the construction of a fairer and more harmonious society. Understanding the role that law brings to social life is essential to analyze how societies transform and develop over time, making law not just an abstract right, but also a mirror of needs, values ​​and desires. fundamental elements of a humanitarian community. We can examine how law undergoes significant changes according to actions within a society, however, law changes and adapts. It was possible to conclude, in short, the ability to see not only external changes in laws and norms, but also the fullest and most significant movements that highlight the course of society.